A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages Secretary of State on the co-ordination of the hospital and consultant services in each region. (ii) Joint Hospitals Boards will be formed by combination of neighbouring major local authorities (county councils and town councils of large burghs) within the regions to ensure an adequate hospital service in their areas. The Boards will take over all responsibility for the hospital services of the constituent authorities (including services like the tuberculosis dispensaries, which essentially belong to the hospital and consultant field) and will also arrange with voluntary hospitals. (iii) The joint boards will prepare a scheme for the hospital service in their areas and submit this to the Secretary of State, who will consult the Regional Hospitals Advisory Council before deciding to approve or amend it. The powers of the Secretary of State will be strengthened to enable him to require major local authorities to combine for any purpose proved necessary after local enquiry. (iv) Education authorities (county councils and town councils of four cities) will retain responsibility for the school health service and clinics, until the medical treatment part of the school service can be absorbed in the wider health service. Existing major health authorities (county councils and town councils of large burghs) will normally retain responsibility for the ordinary local clinic and similar services; the necessary co-ordination will be secured through their membership of the joint hospital boards and through the Local Medical Services Committees (below). (v) Local Medical Services Committees — advisory bodies consisting of professional and local authority representatives — will be set up over the same areas as the Joint Hospitals Boards. The Committees will advise the Secretary of State on local administration of the general practitioner service and will provide liaison between the different branches of the service. It is estimated that the cost of the new National Health Service will be about £148,000,000 a year compared with about £61,000,000 spent from public funds on the present health services. The cost will be met from both central and local public funds. The arrangements as affecting the various local authorities and the voluntary hospitals are fully considered in the White Paper and more briefly in this paper. Crown Copyright Reserved. To be purchased directly from H.M. STATIONERY OFFICE at the following addresses: York House, Kmgsway, London, W.C.2 ; 120 George Street, Edinburgh 2 ; 39-41 King Street, Manchester 2 ; : 1 St. Andrew's Crescent. Cardiff ; 80 Chichester Street, Belfast; or through any bookseller. Price 3 d. net. N. & P.—51/2490 32 S.O. Code No. 32—358* 36/H24/41